PENERAPAN COOPERATIVE LEARNING TIPE JIGSAW UNTUK MENINGKATKAN PEMAHAMAN DAN KETERAMPILAN MAHASISWA - Setiani, Rediana (Dinamika Pendidikan, 2009)
The objectives of this study are: (1) to improve studentsÃ¢â¬â¢ understanding in Accounting Computer subject mahasiswa pada mata kuliah Komputer Akuntansi, (2) to improve studentsÃ¢â¬â¢ skills in Accounting Computer subject. The subject of this research is accounting students of education program that take accounting computer subject. This research is class action research consists ofÃÂ  3 cycles. The given action in the first cycle according to the result of beginning reflection. In every cycle consists of 4 stages that are planning, actuating, observation, and reflection. This research reached standardized indicator that 70% students have minimum score that was 71 (B). It showed that the application of cooperative learning jigsaw type can improve the studentsÃ¢â¬â¢ ability in a computer accounting subject. ÃÂ  Key Words : Cooperative Learning, Jigsaw, the studentsÃ¢â¬â¢ understanding, creativity